2021
DOI: 10.3390/biomedicines9080851
|View full text |Cite
|
Sign up to set email alerts
|

Noble Metals for Modern Implant Materials: MOCVD of Film Structures and Cytotoxical, Antibacterial, and Histological Studies

Abstract: This work is aimed at developing the modification of the surface of medical implants with film materials based on noble metals in order to improve their biological characteristics. Gas-phase transportation methods were proposed to obtain such materials. To determine the effect of the material of the bottom layer of heterometallic structures, Ir, Pt, and PtIr coatings with a thickness of 1.4–1.5 μm were deposited by metal–organic chemical vapor deposition (MOCVD) on Ti6Al4V alloy discs. Two types of antibacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 63 publications
4
29
0
Order By: Relevance
“…Silver nanoparticles (AgNPs) have been studied in greater depth than CNFs. They are also cost-effective and possess excellent antimicrobial properties [ 20 , 21 , 22 , 23 , 24 ]. In fact, AgNPs are already broadly used in wound dressings for healing processes and treating burns in biomedicine as well as in the food and textile industries and in paints, household products, catheters, implants, and cosmetics and in combination with many types of materials to prevent infection [ 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Silver nanoparticles (AgNPs) have been studied in greater depth than CNFs. They are also cost-effective and possess excellent antimicrobial properties [ 20 , 21 , 22 , 23 , 24 ]. In fact, AgNPs are already broadly used in wound dressings for healing processes and treating burns in biomedicine as well as in the food and textile industries and in paints, household products, catheters, implants, and cosmetics and in combination with many types of materials to prevent infection [ 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…determination (Kofler table). The detailed synthesis and identification of the gold precursor were described in our previous work [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this method, volatile precursors (noble metal complexes with organic ligands) are heated in a vacuum reactor to transfer them to the gas phase and then transported in a carrier gas flow to the deposition zone, where an activated chemical reaction of decomposition of precursor vapors occurs on the heated surface of the implant with the formation of a metal coating and removal of gaseous reaction products. This method has already been successfully used and described in detail in our previous publication [ 24 ]. The method of physical vapor deposition (PVD) was used to deposit silver nanoparticles onto the film structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 91 Innovative research revealed that synthesized nanocomposites (Ag/Pt, Ag/Ir, Ag/PtIr, Au/Pt, Au/Ir, and Au/PtIr) presented antibacterial and cytotoxic activity. 92 High antibacterial activity was presented by AuNPs synthesized via epigallocatechin 3-gallate. The produced nanocomposites showed antibacterial properties against S. aureus , Enterococcus faecalis , P. aeruginosa and E. coli ( Table 3 ).…”
Section: Gold Nanoparticlesmentioning
confidence: 99%